Influence of Agroforestry Systems and oil palm (Elaeis guineensis) monoculture on the activity of arbuscular mycorrhizal fungi in the Amazon - Maia, Rodrigo da Silva; Miranda, Gabriele Carolina Nunes; Almeida, Adler Glenda Gaia de; Silva, Taynara Cristina de Sousa; Pinto, Rayane Caroline Pinto; Vasconcelos, Steel Silva (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2023)
In the Amazon, the conventional oil palm system (Elaeis guineensis) is changing the landscape through increased deforestation, loss of biodiversity and increased soil erosion. An alternative cropping system based on oil palm insertion in Agroforestry Systems (AS) was proposed in the city of Tomé-Açu (state of Pará, Brazil) in order to evaluate the impact of this system on soil quality compared to conventional cultivation (monoculture). The objective of this study was to evaluate the impacts of two types of differents AS (with high and low plant diversity) on the percentage of mycorrhizal colonization (PMC) on the oil palm and the spore density in the soil in relation to the conventional crop. The PMC was evaluated in fine roots (diameter ≤ 2 mm) and soil samples (0-10 cm) were collected. Mycorrhizal colonization in oil palm cultivation inserted in AS was higher in relation to monoculture, on the other hand spore density was higher in the conventional system. Soil management based on agroforestry systems with high or low diversity of plant species may contribute to mycorrhizal colonization in the oil palm of the Amazon.